Morphology and Optical Properties Analysis of Cu2+ Doped ZnO for Preparation Dye Sensitized Solar Cell (DSSC) - Idawati Supu; Dewa Gede Eka Setiawan; Muh. Fachrul Latief; Sri Yanti N Ismail; Yita Irmala Sari (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
This research reported Cu2+ un-doped (pure) and doped ZnO semiconductors with variations in Cu2+ concentrations of 3%, 4% and 5% through the sol gel method which aims to determine the morphology and optical properties of ZnO has been investigated. In addition, ZnO film was coated using the doctor blade method with the addition of chlorophyll as a dye sensitizer. Morphological and elemental content tests were carried out using SEM and EDS. The optical properties were analyzed by taking Transmittance data using a UV-Vis Spectrophotometer. SEM analysis with 9900X magnification showed that all samples had small grain sizes and the pores formed were uneven (heterogeneous). The EDS analysis showed that all samples had a higher concentration of zinc by weight than oxygen. UV-Vis Spectrophotometer analysis shows that the transmittance value without dye is lower than using Dye. The addition of Cu2+ concentration affects the morphology and optical properties of ZnO. The higher the addition of Cu2+ added chlorophyll, the higher the absorbance value, so that the transmittance value decreases. The addition of 4% concentration showed the maximum value of chlorophyll as a sensitizer.